Diagnostic Value of 18F-FDG PET/MRI for Revised 2018 FIGO Staging in Patients with Cervical Cancer - Hideaki Tsuyoshi; Tetsuya Tsujikawa; Shizuka Yamada; Hidehiko Okazawa; Yoshio Yoshida (Diagnostics, 2021)
Purpose: To evaluate the diagnostic potential of PET/MRI with 18F-fluorodeoxyglucose (18F-FDG) in cervical cancer based on the revised 2018 International Federation of Gynecology and Obstetrics (FIGO) staging system. Materials and Methods: Seventy-two patients with biopsy-proven primary cervical cancer underwent pretreatment 18F-FDG PET/MRI, CT, and pelvic MRI. The diagnostic performance of 18F-FDG PET/MRI and MRI for assessing extent of the primary tumor and 18F-FDG PET/MRI and CT for assessing nodal and distant metastases was evaluated by two experienced readers. Histopathological and follow-up imaging results were used as the gold standard. McNemar test was employed for statistical analysis. Results: Accuracy for the invasion of vagina, parametrium, side wall, and adjacent organs was 97.2%, 93.1%, 97.2%, and 100% for 18F-FDG PET/MRI; and 97.2%, 91.7%, 97.2%, and 100% for pelvic MRI, respectively (p > 0.05). Patient-based accuracy for metastasis to pelvic and paraaortic lymph nodes and distant organs was 95.8%, 98.6%, and 100% for 18F-FDG PET/MRI; and 83.3%, 95.8%, and 97.2% for CT, respectively; metastasis to pelvic lymph nodes was statistically significant (p < 0.01). Lesion-based sensitivity, specificity, and accuracy for lymph nodes were 83.3%, 95.9%, and 94.8% for 18F-FDG PET/MRI; and 29.2%, 98.9% and 93.1% for CT, respectively; sensitivity was statistically significant (p < 0.001). After excluding patients diagnosed by conization, accuracy for revised FIGO staging 2018 was significantly better for 18F-FDG PET/MRI (82.1%) than for CT and MRI (60.7%) (p < 0.01). Conclusions: 18F-FDG PET/MRI offers higher diagnostic value for revised 2018 FIGO staging, suggesting that 18F-FDG PET/MRI might provide an optimal diagnostic strategy for preoperative staging.